Novel role of the clustered miR‐23b‐3p and miR‐27b‐3p in enhanced expression of fibrosis‐associated genes by targeting TGFBR3 in atrial fibroblasts. Issue 5 (7th February 2019) - Yang, Zhenzhen; Xiao, Zhen; Guo, Huiming; Fang, Xianhong; Liang, Jingnan; Zhu, Jiening; Yang, Jing; Li, Hui; Pan, Rong; Yuan, Shujing; Dong, Wenyan; Zheng, Xi‐Long; et al.
Abstract: Atrial fibrillation (AF) is the most common type of arrhythmia in cardiovascular diseases. Atrial fibrosis is an important pathophysiological contributor to AF. This study aimed to investigate the role of the clustered miR‐23b‐3p and miR‐27b‐3p in atrial fibrosis. Human atrial fibroblasts (HAFs) were isolated from atrial appendage tissue of patients with sinus rhythm. A cell model of atrial fibrosis was achieved in Ang‐II‐induced HAFs. Cell proliferation and migration were detected. We found that miR‐23b‐3p and miR‐27b‐3p were markedly increased in atrial appendage tissues of AF patients and in Ang‐II‐treated HAFs. Overexpression of miR‐23b‐3p and miR‐27b‐3p enhanced the expression of collagen, type I, alpha 1 (COL1A1), COL3A1 and ACTA2 in HAFs without significant effects on their proliferation and migration. Luciferase assay showed that miR‐23b‐3p and miR‐27b‐3p targeted two different sites in 3ʹ‐UTR of transforming growth factor (TGF)‐β1 receptor 3 (TGFBR3) respectively. Consistently, TGFBR3 siRNA could increase fibrosis‐related genes expression, along with the Smad1 inactivation and Smad3 activation in HAFs. Additionally, overexpression of TGFBR3 could alleviate the increase of COL1A1, COL3A1 and ACTA2 in HAFs after transfection with miR‐23b‐3p and miR‐27b‐3p respectively. Moreover, Smad3 was activated in HAFs in response to Ang‐II treatment and inactivation of Smad3 attenuated up‐regulation of miR‐23b‐3p and miR‐27b‐3p in Ang‐II‐treated HAFs. Taken together, these results suggest that the clustered miR‐23b‐3p and miR‐27b‐3p consistently promote atrial fibrosis by targeting TGFBR3 to activate Smad3 signalling in HAFs, suggesting that miR‐23b‐3p and miR‐27b‐3p are potential therapeutic targets for atrial fibrosis.